Thermodynamic Feasibility of the Black Sea CH4 Hydrate Replacement by CO2 Hydrate - Bjørn Kvamme; Atanas Vasilev (Energies, 2023)
There is an international consensus that reductions of CO2 emissions are needed in order to reduce global warming. So far, underground aquifer storage of CO2 is the only commercially active option, and it has been so since 1996, when STAOIL started injecting a million tons of CO2 per year into the Utsira formation. Storage of CO2 in the form of solid hydrate is another option that is safer. Injection of CO2 into CH4 hydrate-filled sediments can lead to an exchange in which the in situ CH4 hydrate dissociates and releases CH4. Two types of additives are needed, however, to make this exchange feasible. The primary objective of the first additive is related to hydrodynamics and the need to increase injection gas permeability relative to injection of pure CO2. This type of additive is typically added in amounts resulting in concentration ranges of additive in the order of tens of percentages of CO2/additive mixture. These additives will, therefore, have impact on the thermodynamic properties of the CO2 in the mixture. A second additive is added in order to reduce the blocking of pores by new hydrates created from the injection gas and free pore water. The second additive is a surfactant and is normally added in ppm amounts to the gas mixture. A typical choice for the first additive has been N2. The simple reasons for that are the substantial change in rheological properties for the injection gas mixture and a limited, but still significant, stabilization of the small cavities of structure I. There are, however, thermodynamic limitations related to adding N2 to the CO2. In this work, we discuss a systematic and consistent method for the evaluation of the feasibility of CO2 injection into CH4 hydrate-filled reservoirs. The method consists of four thermodynamic criterions derived from the first and second laws of thermodynamics. An important goal is that utilization of this method can save money in experimental planning by avoiding the design of CO2 injection mixtures that are not expected to work based on fundamental thermodynamic principles. The scheme is applied to hydrates in the Black Sea. Without compositional information and the knowledge that there is some verified H2S in some sites, we illustrate that the observed bottom hydrate stability limits are all with hydrate stability limits of hydrates containing from 0 to 3 mole% H2S. A limited number of different injection gas mixtures has been examined, and the optimum injection gas composition of 70 mole% CO2, 20 mole% N2, 5 mole% CH4, and 5 mole% C2H6 is feasible. In addition, a surfactant mixture is needed to reduce blocking hydrate films from injection gas hydrate.